2020
DOI: 10.1177/0363546520976626
|View full text |Cite
|
Sign up to set email alerts
|

Unplanned Emergency Visits and Admissions After Orthopaedic Ambulatory Surgery in the First 2 Years of Operation of a University Ambulatory Surgery Center

Abstract: Background: Ambulatory surgeries have increased in recent decades to help improve efficiency and cost; however, there is a potential need for unplanned postoperative admission, clinic visits, or evaluation in the emergency department (ED). Purpose/Hypothesis: The purpose was to determine the frequency, reasons, and factors influencing hospitalizations, return to clinic, and/or ED encounters within 24 hours of ambulatory surgery. The time frame for data collection was the first 2 years of operation of a univers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
0
3
2
Order By: Relevance
“…The ED utilization rates after surgeries for sports-related injuries were slightly lower compared with those in previous studies on postoperative ED utilization rates of outpatient rotator cuff repair (3.2% 7 days and 5.0% 30 days), 17 elective hip arthroscopy (1.8% 7 days, 3.5% 30 days, and 6.6% 90 days), 15 ankle surgery (7.2% 30 days), 18 and outpatient hand surgery (1.8% 7 days and 4.4% 30 days). 16 For sports medicine procedures, a recent study by Brown et al reported an unplanned medical care utilization rate of 0.75% within the 24-hour postoperative period, 30 which is lower than the ED utilization rates in this study but is primarily representative of the immediate postoperative period. Of note, postoperative ED utilization rates for sports-related injuries were markedly lower than the 4.5 to 13.8% reported in the total joint arthroplasty literature, 12,[21][22][23][24] which can be partially explained by the invasive nature of joint arthroplasty procedures and their higher postoperative pain and complication profiles.…”
Section: Discussioncontrasting
confidence: 66%
“…The ED utilization rates after surgeries for sports-related injuries were slightly lower compared with those in previous studies on postoperative ED utilization rates of outpatient rotator cuff repair (3.2% 7 days and 5.0% 30 days), 17 elective hip arthroscopy (1.8% 7 days, 3.5% 30 days, and 6.6% 90 days), 15 ankle surgery (7.2% 30 days), 18 and outpatient hand surgery (1.8% 7 days and 4.4% 30 days). 16 For sports medicine procedures, a recent study by Brown et al reported an unplanned medical care utilization rate of 0.75% within the 24-hour postoperative period, 30 which is lower than the ED utilization rates in this study but is primarily representative of the immediate postoperative period. Of note, postoperative ED utilization rates for sports-related injuries were markedly lower than the 4.5 to 13.8% reported in the total joint arthroplasty literature, 12,[21][22][23][24] which can be partially explained by the invasive nature of joint arthroplasty procedures and their higher postoperative pain and complication profiles.…”
Section: Discussioncontrasting
confidence: 66%
“…Contrary to our study, most unplanned ED/UC visits reported in the literature are accompanied by a chief report of postoperative pain. 18 , 20 , 21 , 23 Only 9.0% of the patients presenting to an ED/UC visit in our study stated a pain-specific report. The most frequently reported reports prompting ED/UC visits in our study were medication-related concerns (13.2%).…”
Section: Discussioncontrasting
confidence: 52%
“…Multiple studies have quantified the frequency of and identified risk factors contributing to unplanned ED/UC visits after outpatient orthopaedic surgeries. 11 , 18 , 20 21 22 23 24 Although the recorded incidence of ED/UC visit is generally lower, variability exists within the literature. 11 , 18 , 20 21 22 23 24 Sivasundaram et al 20 reported a slightly lower incidence of ED visit utilization (4.4%) within 30 days of outpatient surgery, compared with our study (5.4%), and 6.9% of patients presented to an unplanned ED within 7 days of surgery in the study of Navarro et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the procedures that qualify for stay in the Care Hotel are all considered one-night observation in nature, some surgical teams may have chosen to emphasize the risk of post-procedural complications differently based on the patients’ comorbidities. Overall, less complex and healthier patients are more likely to be discharged to home as opposed to be observed in a hospital, 17 since higher ASA PS Classes have been associated with complications, 13 unplanned readmissions, 18,19 block failures, 20 and a higher mortality risk in this setting. 13 These are some of the reasons why some surgical teams consider ASA PS Classes 1 and 2 a part of the inclusion criteria for immediate discharge after surgery, 21 while others extend it to Class 3 based on the low risk of complications following a specific procedure.…”
Section: Discussionmentioning
confidence: 99%